2012
DOI: 10.1016/j.otsr.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Total talar fracture – Long-term results of internal fixation of talar fractures. A multicentric study of 114 cases

Abstract: The complication rate for talar fractures was high, mostly due to osteonecrosis and osteoarthritis; these conditions had an impact on the final outcome. The outcome could be improved by better evaluating these fractures with a CT scan, developing dual surgical approaches to best preserve the bone vascular supply and achieve better reduction, and improving the internal fixation hardware, especially the use of plates for comminuted fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 19 publications
6
60
0
Order By: Relevance
“…Many studies have demonstrated that the main reason for poor outcomes is post-traumatic arthritis, which is dependent on malunion and damage to the cartilage at the time of injury [15,20,21]. Anatomical reduction is difficult to obtain owing to the complex anatomy of the talus and comminuted nature of the fractures [8]. A dual approach can provide better control during reduction because the medial and lateral faces of the talar neck are exposed, so many surgeons recommend dual approaches to obtain anatomical reduction and axial alignment [15,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that the main reason for poor outcomes is post-traumatic arthritis, which is dependent on malunion and damage to the cartilage at the time of injury [15,20,21]. Anatomical reduction is difficult to obtain owing to the complex anatomy of the talus and comminuted nature of the fractures [8]. A dual approach can provide better control during reduction because the medial and lateral faces of the talar neck are exposed, so many surgeons recommend dual approaches to obtain anatomical reduction and axial alignment [15,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Avascular necrosis was defined as any area of increased density of the talar dome relative to the adjacent structures [3]. The clinical outcome was evaluated using the AnkleHindfoot Scale of the American Orthopaedic Foot and Ankle Society (AOFAS) [7], SF-36 and patient satisfaction [8].…”
Section: Methodsmentioning
confidence: 99%
“…1 Late complications include osteonecrosis, posttraumatic arthritis, osteomyelitis, stiffness, malunion, and nonunion. [1][2][3][4] Posttraumatic arthritis of the subtalar joint is the most common late complication and can involve the ankle, subtalar, and/or talonavicular joint. 2 This can present as pain and stiffness of the involved joint.…”
mentioning
confidence: 99%
“…The talus has a unique anatomic shape and function. Without direct muscle attachments, it provides the junction between the lower leg and the foot (2,3). Displacement of the fragments leads to subluxation of the subtalar joint, and most researchers have recommended open reduction and internal fixation for displaced fractures (2,(4)(5)(6).…”
mentioning
confidence: 99%
“…The process of open reduction and internal fixation has historically been thought to facilitate revascularization and prevent osteonecrosis (2)(3)(4)(5). Variable-pitch screws have some biomechanical advantages compared with conventional screws in talus fracture fixation.…”
mentioning
confidence: 99%